Dielectric ceramic composition

By using a perovskite structure and specific metal element ratio design in the dielectric ceramic composition, the problem of low AC breakdown electric field in the prior art is solved, and a dielectric ceramic composition with high insulation resistance and low loss is achieved.

CN116598045BActive Publication Date: 2024-12-20TDK CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211590424.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-02-14
Filing Date
2022-12-12
Publication Date
2024-12-20
Estimated Expiration
2042-12-12

AI Technical Summary

Technical Problem

The existing dielectric ceramic compositions are insufficient in terms of AC breakdown electric fields and are difficult to maintain high insulation resistance.

Method used

Dielectric ceramic composition using a perovskite structure represented by the general formula AMO3, the A site contains Ba, the M site contains Ti, Fe and Mn are added as the fourth A subcomponent, and the second is optimized under the calculation of metal element to the proportion of the sixth sub-component to increase the relative dielectric constant and AC breakdown electric field.

Benefits of technology

High insulation resistance and improved AC breakdown electric field, reduced dielectric loss, and optimized the temperature characteristics of the electrostatic capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116598045B_ABST
    Figure CN116598045B_ABST
Patent Text Reader

Abstract

The present invention provides a method having a general formula AMO 3 The dielectric ceramic composition of the main component particles of the perovskite structure represented by the present invention comprises Ba at the A site and Ti at the M site. The dielectric ceramic composition comprises a fourth A subcomponent, and the fourth A subcomponent comprises Fe and Mn. The molar ratio of Mn to the total of Fe and Mn is 0.18 to 0.65 in terms of metal element conversion.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention claims priority based on Japanese Patent Application No. 2022-020707 filed on February 14, 2022, the entire disclosure of which is incorporated into this specification by reference. Technical Field

[0002] The present invention relates to a dielectric ceramic composition. Background Art

[0003] For example, Japanese Patent Application Laid-Open No. 102105 discloses a dielectric ceramic composition containing niobium oxide, cobalt oxide, and manganese oxide in order to achieve a high dielectric constant.

[0004] However, the dielectric ceramic composition disclosed in Japanese Patent Application Laid-Open No. 63-102105 has a technical problem that the AC breakdown electric field is low. Summary of the invention

[0005] The technical problem that the invention is intended to solve

[0006] The present invention has been made in view of such actual circumstances, and an object of the present invention is to provide a dielectric ceramic composition capable of maintaining high insulation resistance and improving an AC breakdown electric field.

[0007] Means for solving technical problems

[0008] The dielectric ceramic composition of the present invention is a dielectric ceramic composition having main component particles of a perovskite structure represented by the general formula AMO3.

[0009] The A site contains Ba,

[0010] The M site contains Ti,

[0011] The dielectric ceramic composition contains a fourth A subcomponent,

[0012] The fourth A subcomponent contains Fe and Mn.

[0013] The molar ratio of Mn to the total of Fe and Mn is 0.18 to 0.65 in terms of metal element conversion.

[0014] The present invention can provide a dielectric ceramic composition which maintains high insulation resistance and improves AC breakdown electric field.

[0015] The dielectric ceramic composition of the present invention preferably contains 0 to 10 mol parts of a second auxiliary component per 100 mol parts of the element at the M site in terms of metal element, and the second auxiliary component is preferably at least one selected from Nb, Mo, Ta, W, Sn and Bi.

[0016] As a result, the relative dielectric constant of the dielectric ceramic composition is improved.

[0017] The dielectric ceramic composition according to the present invention preferably contains 0.01 to 2 mol parts of the third auxiliary component per 100 mol parts of the M site element in terms of metal element. The third auxiliary component is preferably at least one selected from Sm, Nd and La.

[0018] Thus, the temperature characteristics of the capacitance of the dielectric ceramic composition are good. Here, the temperature characteristics of the capacitance are good means that the absolute value of the capacitance change rate (TC) is small.

[0019] The dielectric ceramic composition according to the present invention may contain a fourth B subcomponent, and the fourth B subcomponent may contain at least one selected from the group consisting of Co, Zn, Ni, and Cr.

[0020] The dielectric ceramic composition according to the present invention preferably contains 0.02 to 2.2 mol parts in total of the fourth A subcomponent and the fourth B subcomponent per 100 mol parts of the element at the M site in terms of metal elements.

[0021] Therefore, the temperature characteristics of the capacitance of the dielectric ceramic composition are good.

[0022] The dielectric ceramic composition according to the present invention preferably contains 0.08 mol parts or more of the sixth subcomponent per 100 mol parts of the M-site element in terms of metal element. The sixth subcomponent is preferably at least one selected from Si, Al and B.

[0023] As a result, the AC breakdown electric field of the dielectric ceramic composition is further improved.

[0024] In the dielectric ceramic composition according to the present invention, the molar ratio of the total of Ba, Ca, and Sr to the total of Ti and Zr is preferably 0.98 to 1.02 in terms of metal elements.

[0025] As a result, the relative dielectric constant, insulation resistance, and AC breakdown electric field of the dielectric ceramic composition can be further improved, thereby reducing dielectric loss.

[0026] The dielectric ceramic composition of the present invention preferably contains 0 to 3 mol parts of a fifth A subcomponent relative to 100 mol parts of the element at the M site in terms of metal element conversion, and the fifth A subcomponent is preferably at least one selected from Ba, Ca and Sr. It is preferred that the dielectric ceramic composition contains 0 to 2.5 mol parts of a fifth B subcomponent relative to 100 mol parts of the element at the M site in terms of metal element conversion, and the fifth B subcomponent is preferably at least one selected from Ti and Zr.

[0027] Thus, the relative dielectric constant, insulation resistance and AC breakdown electric field of the dielectric ceramic composition can be further improved, and the dielectric loss can be reduced. In addition, this means that even if the molar ratio (A / M) of the element at the A site to the element at the M site of the main component raw material changes, as long as the molar ratio {(Ba+Ca+Sr) / (Ti+Zr)} of the total of Ba, Ca and Sr in terms of metal elements to the total of Ti and Zr in the dielectric ceramic composition itself is controlled within a preferred range by adding the fifth A subcomponent and / or the fifth B subcomponent, the relative dielectric constant, insulation resistance and AC breakdown electric field can be improved, thereby reducing the dielectric loss. That is, the preferred range of the addition amount of the fifth A subcomponent and the fifth B subcomponent will change depending on the A / M ratio of the main component raw material, but the preferred range of {(Ba+Ca+Sr) / (Ti+Zr)} of the dielectric ceramic composition itself will not change.

[0028] The dielectric ceramic composition according to the present invention preferably contains less than 0.3 mol parts of the first auxiliary component per 100 mol parts of the element at the M site in terms of metal element, and the first auxiliary component is preferably Mg.

[0029] Therefore, the temperature characteristics of the capacitance of the dielectric ceramic composition are good.

[0030] The electronic component according to the present invention has a dielectric layer composed of a dielectric ceramic composition obtained from the above-mentioned dielectric ceramic composition.

[0031] The electronic component according to the present invention is not particularly limited, and examples thereof include a single-board ceramic capacitor and a multilayer ceramic capacitor. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a front view of a ceramic capacitor according to one embodiment of the present invention.

[0033] Figure 2 It is a side cross-sectional view of a ceramic capacitor according to one embodiment of the present invention.

[0034] Explanation of symbols:

[0035] 2... ceramic capacitor; 4... protective resin; 6, 8... lead terminals; 10... dielectric layer; 12, 14... terminal electrodes. DETAILED DESCRIPTION

[0036] Ceramic capacitors 2

[0037] A ceramic capacitor 2 is shown as an example of an electronic component according to this embodiment. Figure 1 and Figure 2 .like Figure 1 and Figure 2 As shown, the ceramic capacitor 2 according to the present embodiment includes a dielectric layer 10 , a pair of terminal electrodes 12 , 14 formed on surfaces opposite to the dielectric layer 10 , and lead terminals 6 , 8 respectively connected to the terminal electrodes 12 , 14 , which are covered with a protective resin 4 .

[0038] The shape of the ceramic capacitor 2 can be appropriately determined according to the purpose or use, and is preferably a single-plate capacitor with a disc-shaped dielectric layer 10. In addition, its size can be appropriately determined according to the purpose or use, and the diameter is preferably 3 to 20 mm, more preferably 5 to 20 mm, and further preferably 5 to 15 mm.

[0039] The terminal electrodes 12 and 14 are made of a conductive material. Examples of the conductive material used for the terminal electrodes 12 and 14 include Cu, Cu alloys, Ag, Ag alloys, and In—Ga alloys.

[0040] The thickness of the dielectric layer 10 is not particularly limited and may be appropriately determined according to the application, but is preferably 0.1 to 3 mm, more preferably 0.3 to 2 mm. When the thickness of the dielectric layer 10 is within such a range, it can be applied to medium and high voltage applications.

[0041] According to this embodiment, the capacitor can be miniaturized.

[0042] The dielectric layer 10 is composed of a dielectric ceramic composition according to the present embodiment. When A represents an A-site element, M represents an M-site element, and O represents an oxygen element, the dielectric ceramic composition according to the present embodiment has main component particles of a perovskite structure represented by the general formula AMO3.

[0043] Here, the "main component of the dielectric ceramic composition" is a component that accounts for 90% by mass or more of the dielectric ceramic composition. That is, the "main component particles" in this embodiment are particles containing such a main component. Therefore, a part of the auxiliary component can be dissolved in the main component particles, and the main component particles can also form a core-shell structure of the main component and the auxiliary component.

[0044] The element of the A site includes Ba. The element of the A site may include Ca and / or Sr in addition to Ba.

[0045] The element at the M site includes Ti. The element at the M site may include Zr in addition to Ti.

[0046] The dielectric ceramic composition according to the present embodiment may contain Mg as a first auxiliary component. The dielectric ceramic composition according to the present embodiment preferably contains less than 0.3 mol parts of the first auxiliary component per 100 mol parts of the M site element in terms of metal element, and more preferably contains 0 to 0.2 mol parts.

[0047] The dielectric ceramic composition according to the present embodiment may contain a second auxiliary component. The second auxiliary component is at least one selected from the group consisting of Nb, Mo, Ta, W, Sn, and Bi.

[0048] The dielectric ceramic composition according to the present embodiment preferably contains 0 to 10 mol parts of the second auxiliary component per 100 mol parts of the element at the M site in terms of metal element, and more preferably contains 1 to 3 mol parts.

[0049] The dielectric ceramic composition according to the present embodiment preferably contains a third auxiliary component. The third auxiliary component is at least one selected from the group consisting of Sm, Nd, and La, and is preferably Sm.

[0050] The dielectric ceramic composition according to the present embodiment preferably contains 0.01 to 2 mol parts, more preferably 0.3 to 1.5 mol parts, of the third auxiliary component per 100 mol parts of the M-site element in terms of metal element.

[0051] The dielectric ceramic composition according to the present embodiment contains a fourth A subcomponent. The fourth A subcomponent is Fe and Mn.

[0052] In the present embodiment, the molar ratio of Mn to the total of Fe and Mn {Mn / (Fe+Mn)} in terms of metal element is preferably 0.18 to 0.65, and more preferably 0.3 to 0.6.

[0053] The dielectric ceramic composition according to the present embodiment may contain a fourth subcomponent B. The fourth subcomponent B is at least one selected from the group consisting of Co, Zn, Ni, and Cr, and is preferably Co.

[0054] The dielectric ceramic composition according to the present embodiment preferably contains 0.02 to 2.2 mol parts, more preferably 0.2 to 1.0 mol parts, of the fourth A subcomponent and the fourth B subcomponent in total per 100 mol parts of the M site element in terms of metal element.

[0055] The dielectric ceramic composition according to the present embodiment preferably contains a fifth A subcomponent. The fifth A subcomponent is at least one selected from the group consisting of Ba, Ca, and Sr, and is preferably Sr.

[0056] The dielectric ceramic composition according to the present embodiment preferably contains a fifth subcomponent B. The fifth subcomponent B is at least one selected from the group consisting of Ti and Zr, and is preferably Ti.

[0057] The molar ratio of the total of Ba, Ca and Sr to the total of Ti and Zr in the dielectric ceramic composition according to the present embodiment in terms of metal elements {(Ba+Ca+Sr) / (Ti+Zr)} is preferably 0.98 to 1.02, and more preferably 0.990 to 1.010. The numerator (Ba+Ca+Sr) / (Ti+Zr) of (Ba+Ca+Sr) / (Ti+Zr) is the total of the components contained in the A site of the main component and the components contained in the fifth A subcomponent. In addition, the denominator (Ti+Zr) of (Ba+Ca+Sr) / (Ti+Zr) is the total of the components contained in the M site of the main component and the components contained in the fifth B subcomponent.

[0058] The dielectric ceramic composition according to the present embodiment preferably contains a sixth subcomponent. The sixth subcomponent is at least one selected from Si, Al, and B, and is preferably Si and / or Al.

[0059] The dielectric ceramic composition according to the present invention preferably contains 0.08 mol parts or more of the sixth auxiliary component per 100 mol parts of the element at the M site in terms of metal element, and more preferably 0.2 to 1.5 mol parts.

[0060] Method for manufacturing ceramic capacitors

[0061] Next, a method for manufacturing a ceramic capacitor will be described.

[0062] First, after firing, the formation Figure 2 The dielectric layer 10 is shown as a dielectric ceramic composition powder.

[0063] Prepare the raw material of the main component and the raw materials of the first to sixth subcomponents. The raw material of the main component is not particularly limited, and can be appropriately selected from the oxides or composite oxides of the above-mentioned main components, or various compounds that become these oxides or composite oxides by calcination, such as carbonates, nitrates, hydroxides, organic metal compounds, etc. As the raw material of the main component, for example, BaCO3, TiO2, etc. can be used.

[0064] The raw material of the main component may be produced by a solid phase method or a liquid phase method such as a hydrothermal synthesis method or an oxalate method. However, production by a solid phase method is preferred from the viewpoint of production cost.

[0065] The molar ratio of the element at the A site to the element at the M site in the main component raw material (main component raw material A / M) is not particularly limited, and is, for example, 0.990 to 1.005.

[0066] The raw materials of the first to sixth auxiliary components are not particularly limited and can be appropriately selected from oxides or composite oxides of the auxiliary components described above, or various compounds that become these oxides or composite oxides by firing, such as carbonates, nitrates, hydroxides, and organic metal compounds.

[0067] In the method for producing the dielectric ceramic composition according to the present embodiment, first, a raw material of a main component or a raw material of a main component and a raw material of a subcomponent are mixed and wet-mixed using a ball mill using zirconia balls or the like.

[0068] The obtained mixture is granulated and molded, and the obtained molded product is calcined in an air atmosphere to obtain a calcined powder. The calcination conditions include, for example, a calcination temperature of preferably 1100 to 1300° C., more preferably 1150 to 1250° C., and a calcination time of preferably 0.5 to 4 hours.

[0069] Next, the obtained calcined powder is wet-pulverized by a ball mill or the like, and the remaining auxiliary components are mixed and dried to obtain a dielectric ceramic composition powder. As described above, by producing a dielectric ceramic composition powder by a solid phase method, desired properties can be achieved and production costs can be reduced.

[0070] Next, an appropriate amount of binder is added to the obtained dielectric ceramic composition powder, granulated, and the obtained granules are formed into a disk shape having a predetermined size, thereby forming a green compact. Then, the obtained green compact is fired to obtain a sintered body of the dielectric ceramic composition. The firing conditions are not particularly limited, but the holding temperature is preferably 1100 to 1400°C, more preferably 1200 to 1300°C, and the firing atmosphere is preferably air.

[0071] The terminal electrodes are printed on the main surface of the obtained sintered body of the dielectric ceramic composition, and fired as needed to form the terminal electrodes 12 and 14. Then, the lead terminals 6 and 8 are joined to the terminal electrodes 12 and 14 by welding or the like, and finally, the element body is covered with the protective resin 4 to obtain a Figure 1 and Figure 2 The single board type ceramic capacitor 2 is shown.

[0072] The single-board ceramic capacitor 2 according to the present embodiment manufactured in this manner is mounted on a printed circuit board or the like via lead terminals 6 and 8 , and can be used in various electronic devices or the like.

[0073] The dielectric ceramic composition according to the present embodiment has a main component particle of a perovskite structure in which the A site contains Ba and the M site contains Ti and is represented by the general formula AMO3, and the dielectric ceramic composition contains a fourth A subcomponent, and the fourth A subcomponent contains Fe and Mn, and the molar ratio of Mn to the total of Fe and Mn is 0.18 to 0.65. Thus, a dielectric ceramic composition capable of maintaining high insulation resistance and improving AC breakdown electric field can be provided.

[0074] Although one embodiment of the present invention has been described above, the present invention is not limited to the embodiment and can be implemented in various different forms without departing from the gist of the present invention.

[0075] For example, in the above-mentioned embodiment, a single-layer ceramic capacitor having a single dielectric layer is exemplified as an electronic component, but the electronic component involved in the present invention is not limited to a single-layer ceramic capacitor, and may also be a multilayer ceramic capacitor produced by a conventional printing method or a sheet method using a dielectric paste and an electrode paste containing the above-mentioned dielectric ceramic composition.

[0076] Example

[0077] Hereinafter, the present invention will be described based on more detailed examples, but the present invention is not limited to these examples.

[0078] BaCO3 and TiO2 were prepared as raw materials of the main component, respectively. Then, these prepared raw materials were weighed respectively to become the "main component raw materials A / M" shown in each sample of Table 2, Table 4, Table 6, Table 8, Table 10, Table 12, Table 14 and Table 16, and wet mixed by a ball mill using zirconium oxide balls using pure water as a solvent.

[0079] Next, the obtained mixture is dried, and 5% by mass of water is added to granulate and mold. Then, the obtained molded product is calcined in air at 1150°C for 2 hours. The calcined powder is coarsely crushed using a mortar and pestle, and then passed through a sieve to obtain a whole-grain powder. The first to sixth auxiliary components weighed to form the composition shown in Table 1, Table 3, Table 5, Table 7, Table 9, Table 11, Table 13 and Table 15 are added to the whole-grain powder and wet-milled. By drying it, a dielectric ceramic composition powder having the compositions shown in Tables 1 to 16 is obtained.

[0080] 10 parts by mass of polyvinyl alcohol aqueous solution was added to 100 parts by mass of the dielectric ceramic composition powder, and then granulated and passed through a mesh to obtain granulated powder. A pressure of 396 MPa was applied to the obtained granulated powder to obtain a disk-shaped green body with a diameter of 16.5 mm and a thickness of about 1.2 mm.

[0081] The obtained green compact was fired in air at 1200 to 1300° C. for 2 hours to obtain a disk-shaped sintered body.

[0082] Furthermore, Cu electrodes were applied to both sides of the main surface of the obtained sintered body (dielectric layer 10), and sintered at 800° C. for 10 minutes in a reducing atmosphere to obtain a Figure 1 and Figure 2 The disc-shaped ceramic capacitor sample shown in FIG. The thickness of the dielectric layer 10 of the obtained capacitor sample was about 1 mm, and the diameter of the sintered electrode was 12 mm.

[0083] Then, for each capacitor sample obtained, relative dielectric constant, dielectric loss, insulation resistance, AC breakdown electric field and electrostatic capacitance change rate were evaluated using the following methods. The evaluation results are shown in Table 2, Table 4, Table 6, Table 8, Table 10, Table 12, Table 14 and Table 16.

[0084] Relative dielectric constant (εr), dielectric loss (tanδ)

[0085] For the capacitor sample, the electrostatic capacitance and dielectric loss were measured at a reference temperature of 20°C using a digital LCR meter (4278A manufactured by Agilent Technologies) at a frequency of 1kHz and an input signal level (measurement voltage) of 1.0Vrms. The relative dielectric constant ε was calculated from the measured electrostatic capacitance (unitless). The relative dielectric constant is preferably high, and in this embodiment, 1500 or more is set as good.

[0086] Insulation resistance (IR)

[0087] Regarding insulation resistance, the resistance value of the capacitor sample after applying DC 500 V for 60 seconds at room temperature was read using a digital resistance meter (4339B manufactured by Agilent Technologies).

[0088] AC Breakdown Field (ACVB)

[0089] Regarding the AC breakdown electric field (ACVB), an AC electric field is slowly applied to both ends of the capacitor at 100 V / s relative to the capacitor sample, and the electric field value when a leakage current of 100 mA flows is measured as the AC breakdown electric field. The AC breakdown electric field is preferably high, and in this embodiment, 5.0 kV / mm or more is set as good.

[0090] Capacitance change rate (TC)

[0091] For the capacitor samples, the electrostatic capacitance was measured in the temperature range of -25°C to 85°C, and the change rate (in %) of the electrostatic capacitance at -25°C and 85°C relative to the electrostatic capacitance at 20°C was calculated. In this embodiment, the result of the electrostatic capacitance change rate between -15% and 15% was set as good.

[0092]

Table 1

[0093]

[0094]

Table 2

[0095]

[0096]

Table 3

[0097]

[0098]

Table 4

[0099]

[0100]

Table 5

[0101]

[0102]

Table 6

[0103]

[0104]

Table 7

[0105]

[0106]

Table 8

[0107]

[0108]

Table 9

[0109]

[0110]

Table 10

[0111]

[0112]

Table 11

[0113]

[0114]

Table 12

[0115]

[0116]

Table 13

[0117]

[0118]

Table 14

[0119]

[0120]

Table 15

[0121]

[0122]

Table 16

[0123]

[0124] According to Tables 1 and 2, it can be confirmed that when the molar ratio of Mn to the total of Fe and Mn in terms of metal element conversion (Mn / (Fe+Mn)) is 0.18 to 0.65 (sample numbers 1, 3, 4, 7 to 10, 12 to 17), the AC breakdown electric field is higher than when Mn / (Fe+Mn) is 0.77 (sample number 2), 0.90 (sample number 5) and 0.93 (sample number 6).

[0125] It can be confirmed from Tables 1 and 2 that when the molar ratio of Mn to the total of Fe and Mn in terms of metal element conversion (Mn / (Fe+Mn)) is 0.18 to 0.65 (sample numbers 1, 3, 4, 7 to 10, 12 to 17), the insulation resistance is higher than when Mn / (Fe+Mn) is 0.77 (sample number 2) or 0.90 (sample number 5).

[0126] It can be confirmed from Tables 3 and 4 that when the second auxiliary component was contained in an amount of 0 to 10 mol parts in terms of metal element (sample numbers 21 to 25), the relative dielectric constant was higher than when the second auxiliary component was contained in an amount of 11.00 mol parts in terms of metal element (sample number 26).

[0127] According to Tables 5 and 6, it can be confirmed that when the third subcomponent is contained in an amount of 0.01 to 2 mol parts in terms of metal element (sample numbers 31 to 35), the temperature characteristics of the electrostatic capacitance are good compared to when the third subcomponent is not contained (sample number 36) and when the third subcomponent is contained in an amount of 2.10 mol parts in terms of metal element (sample number 37).

[0128] According to Tables 7 and 8, it can be confirmed that when the fourth A subcomponent and the fourth B subcomponent are contained in a total of 0.02 to 2.2 mol parts in terms of metal elements (sample numbers 41 to 44), the temperature characteristics of the electrostatic capacitance are better than when the fourth A subcomponent and the fourth B subcomponent are contained in a total of 0.009 mol parts in terms of metal elements (sample number 45) and 3.00 mol parts in terms of metal elements (sample number 46).

[0129] It can be confirmed from Tables 9 and 10 that when {(Ba+Ca+Sr) / (Ti+Zr)} of the dielectric ceramic composition is 0.98 to 1.02 (sample numbers 51 to 55 and 57), the relative dielectric constant is higher, the dielectric loss is lower, the insulation resistance is higher, and the AC breakdown electric field is higher than when {(Ba+Ca+Sr) / (Ti+Zr)} of the dielectric ceramic composition is 1.021 (sample number 56).

[0130] It can be confirmed from Tables 11 and 12 that when the sixth subcomponent is contained at 0.08 mol parts or more in terms of metal element (sample numbers 62 to 64), the AC breakdown electric field is higher than when the sixth subcomponent is not contained (sample number 61).

[0131] It can be confirmed from Tables 13 and 14 that the insulation resistance is further increased by containing Al as the sixth subcomponent.

[0132] According to Tables 15 and 16, it can be confirmed that when the first auxiliary component is contained in an amount less than 0.3 mol parts in terms of metal element (sample number 81), the temperature characteristics of the electrostatic capacitance are better than when the first auxiliary component is contained in an amount of 0.5 mol parts in terms of metal element (sample number 82).

Claims

1. A dielectric ceramic composition, wherein: The dielectric ceramic composition has main component particles of a perovskite structure represented by the general formula AMO3, The A site contains Ba, The M site contains Ti, In the dielectric ceramic composition, the molar ratio of the total of Ba, Ca and Sr to the total of Ti and Zr is 0.98 to 1.02 in terms of metal elements. The dielectric ceramic composition contains a fourth A subcomponent, The fourth A subcomponent contains Fe and Mn, The molar ratio of Mn to the total of Fe and Mn is 0.18 to 0.65 in terms of metal element conversion. The dielectric ceramic composition contains a fourth B subcomponent, The fourth B subcomponent is at least one selected from Co, Zn, Ni and Cr, The dielectric ceramic composition contains 0.2 to 1.0 mol parts in total of the fourth A subcomponent and the fourth B subcomponent based on 100 mol parts of the M site element in terms of metal element.

2. The dielectric ceramic composition according to claim 1, wherein The dielectric ceramic composition contains 0 to 10 mol parts of the second auxiliary component per 100 mol parts of the element at the M site in terms of metal element. The second auxiliary component is at least one selected from the group consisting of Nb, Mo, Ta, W, Sn, and Bi.

3. The dielectric ceramic composition according to claim 1, wherein The dielectric ceramic composition contains 0.01 to 2 mol parts of the third auxiliary component per 100 mol parts of the element at the M site in terms of metal element. The third auxiliary component is at least one selected from the group consisting of Sm, Nd and La.

4. The dielectric ceramic composition according to claim 1, wherein The dielectric ceramic composition contains a fourth B subcomponent, The fourth B subcomponent contains at least one selected from the group consisting of Co, Zn, Ni and Cr.

5. The dielectric ceramic composition according to claim 1, wherein The dielectric ceramic composition contains 0.02 to 2.2 mol parts of the fourth A subcomponent and the fourth B subcomponent in total per 100 mol parts of the M site element in terms of metal elements. The fourth B subcomponent contains at least one selected from the group consisting of Co, Zn, Ni and Cr.

6. The dielectric ceramic composition according to claim 1, wherein The dielectric ceramic composition contains 0.08 mol parts or more of a sixth auxiliary component per 100 mol parts of the element at the M site in terms of metal element, The sixth subcomponent is at least one selected from Si, Al and B.

7. The dielectric ceramic composition according to claim 1, wherein: The dielectric ceramic composition contains 0 to 3 mol parts of the fifth A subcomponent per 100 mol parts of the element at the M site in terms of metal element. The fifth A subcomponent is at least one selected from Ba, Ca and Sr, The dielectric ceramic composition contains 0 to 2.5 mol parts of the fifth B subcomponent per 100 mol parts of the element at the M site in terms of metal element. The fifth B subcomponent is at least one selected from Ti and Zr.

8. The dielectric ceramic composition according to any one of claims 1 to 7, wherein The dielectric ceramic composition contains less than 0.3 mol parts of the first auxiliary component per 100 mol parts of the element at the M site in terms of metal element. The first auxiliary component is Mg.